The acquisition of information and learning technology skills by FE teachers - Killeen, Martin P. (2009)
The core of this thesis is to investigate the perceptions of teachers in Further Education (FE) when dealing with the continuous change caused by the expansion of information and learning technology (ILT). This thesis also identifies the potential links between the increase in the range and availability of learning technology and the development of self- directed and student-centred learning. It explores the perceptions of practicing teachers with reference to their personal development and if such development indicates compliance with adult learning theory. It also analysis the external pressures placed on FE colleges and their teaching staff due to the development of ILT and the related governmental policy.